Peningkatan Praktek Pencegahan Gejala Pasca-Covid 19 pada Siswa Sekolah Dasar Negeri 69 Gampong Kopelma Darussalam - Mirna Rahmah Lubis; Umi Fathanah; Teuku Maimun; Nurul Aflah (Akademi Farmasi YPPM Mandiri, 2023)
This community service activity is aimed at increasing face-to-face (offline) student practice and knowledge about the practice of preventing post-Covid 19 symptoms. The activity was held at the 69 State Elementary School (SDN) in Gampong Kopelma Darussalam Banda Aceh. The target of this socialization activity is students who spend most of their time playing and studying. The students of SDN 69 are mostly a group of sixth grade students. This service activity began with communication with the teachers at SDN 69 to agree on a time for socialization. Furthermore, at the meeting, brochures were also distributed containing information about the materials needed for the process of making hand sanitizers, manufacturing procedures, theoretical basis, and tricks in making hand sanitizers. Direct practice is carried out with demonstrations of the manufacturing process to finished products accompanied by direct discussions with students. This activity has been able to increase knowledge, insight, and can also improve students' attitudes in Gampong Kopelma Darussalam Banda Aceh, so that it has the opportunity to inhibit the spread and transmission of post-Covid 19 symptoms in Banda Aceh.